18F-FDG-PET/CT for Localizing the Epileptogenic Focus in Patients with Different Types of Focal Cortical Dysplasia - Wang F; Hong ST; Zhang Y; Xing Z; Lin YX (Neuropsychiatric Disease and Treatment, 2024)
Feng Wang,1,* Shu-Ting Hong,1,* Ying Zhang,2 Zhen Xing,3 Yuan-Xiang Lin1 1Neurosurgery Department, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Nuclear Medicine Department, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 3Radiology Department, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuan-Xiang Lin, Neurosurgery Department, the First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, People’s Republic of China, Tel +8613906918894, Fax +86-591-83569369, Email lyx99070@163.comPurpose: To determine the diagnostic and localization value of 18F-fluorodeoxyglucose-positron emission tomography (PET)/computed tomography (CT) in patients with focal cortical dysplasia (FCD) who underwent epilepsy surgery.Methods: One hundred and eight patients with pathologically proven FCD who underwent surgery for refractory epilepsy were retrospectively analyzed. All patients underwent magnetic resonance imaging (MRI), 18F-FDG-PET/CT, and video electroencephalography. An MRI diagnosis of FCD was defined as MRI+. A PET/CT diagnosis of FCD was defined as PET/CT+.Results: MRI and PET/CT detected FCD in 20.37% and 93.52% of patients, respectively. The difference was significant. Twenty-one patients were MRI+/PET+, 80 were MRI-/PET+, six were MRI-/PET-, and one was MRI+/PET-. The MRI positivity rate was lowest in patients with FCD type IIIa (5.6%, P < 0.05). Prevalence of MRI-/PET+ was highest in patients with FCD type IIIa (88.89%, P < 0.05).Conclusion: PET/CT is superior to MRI in detecting FCD. FCD type IIIa was more likely than other types to show MRI-/PET+. This suggests that PET/CT has particular diagnostic value for FCD type IIIa patients with negative MRI findings.Keywords: focal cortical dysplasia, epilepsy, 18F-FDG-PET/CT, pathological types